1999
DOI: 10.1046/j.1471-4159.1999.0730839.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Mesolimbic Dopamine System by Glutamate

Abstract: Abstract:Glutamate has been shown to modulate motor behavior, probably via N-methyl-D-aspartate (NMDA) and ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors that are involved in the control of the mesolimbic dopamine (DA) system, that is, the ventral tegmental area (VTA)-nucleus accumbens (NAC). In the present study, we investigated the effects of uncompetitive (MK-801) and competitive [DL-2-amino-5-phosphonopentanoic acid (AP-5), CGP 40116] NMDA receptor antagonists and NMDA and AMPA on DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 72 publications
6
59
1
Order By: Relevance
“…Overton and Clark (1992) and Georges and Aston-Jones (2002) found that NMDA antagonists administered into the VTA did not decrease basal firing rates of dopamine cells. Furthermore, in vivo microdialysis studies found that AP5 administered into the VTA did not alter extracellular dopamine levels in the VTA's primary terminal fields (ie the nucleus accumbens and prefrontal cortex) (Svensson et al, 1998;Kretschmer, 1999;Fu et al, 2000). It is therefore unlikely that the antagonist effects observed here were a consequence of alterations in dopamine levels.…”
Section: Resultsmentioning
confidence: 99%
“…Overton and Clark (1992) and Georges and Aston-Jones (2002) found that NMDA antagonists administered into the VTA did not decrease basal firing rates of dopamine cells. Furthermore, in vivo microdialysis studies found that AP5 administered into the VTA did not alter extracellular dopamine levels in the VTA's primary terminal fields (ie the nucleus accumbens and prefrontal cortex) (Svensson et al, 1998;Kretschmer, 1999;Fu et al, 2000). It is therefore unlikely that the antagonist effects observed here were a consequence of alterations in dopamine levels.…”
Section: Resultsmentioning
confidence: 99%
“…Since noncompetitive NMDA-receptor antagonists such as MK-801 increase dopamine release in the NAc (Mathe et al, 1996;Yan et al, 1997;Kretschmer, 1999) and stimulate the activity of VTA neurons (French et al, 1993;Murase et al, 1993), the efficacy of MK-801 to increase locomotor activity has also been attributed to increased dopaminergic transmission in mesolimbic structures. In contrast, MK-801-induced hyperlocomotor activity can also occur in the absence of endogenous dopamine (Carlsson and Carlsson, 1989;Chartoff et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…These two opposite modulatory functions of glutamate imply that different subtypes of NMDARs are activated by different inputs to VM DA neurons, so that activation of one subtype of NMDAR initiates DA burst firing whereas activation of another enhances the inhibitory input to DA neurons. This idea is supported by data showing that either activation or blockade of VM NMDARs increases DA burst firing (French et al, 1993), accumbens DA release (Karreman et al, 1996;Kretschmer, 1999), and stimulates forward locomotion (Cornish et al, 2001;Kretschmer, 1999). Blockade of VM NMDARs also acts as a positive reinforcer and sustains self-administration behavior (David et al, 1998).…”
Section: Introductionmentioning
confidence: 90%